Consecuencias de la violencia sexual contra mujeres. - Sánchez Proaño, Daysi Cristina (2016)
This academic essay will show the consequences of sexual violence against women in the city of Quito through the analysis of the theatre play Ensayo para el Vuelo [A Practice to fly], written in the year 2013 by Daysi Sánchez as a communicative and mediation tool. The process of creation, the staging of the play and its implementation to raise awareness regarding this issue among various social groups will be studied. Three stages will be taken into account to analyze the play: the testimonial in which the woman tells the moment when her secret was revealed (the sexual abuse); the dramatic text and its content regarding violence against women in various fields and as a social construction; finally, the way the play is shown in the process of communication mediation.